Framing Effect And Belief Adjustment Model In Investment Judgment - Luciana Spica Almilia; Putri Wulanditya; Riski Aprilia Nita (Jurnal Reviu Akuntansi dan Keuangan, 2020)
This study aims to examine the framing effect and belief adjustment model of the investment decision. A previous study examined partially the effect of framing and belief adjustment models. This research used experiment method. Research method is 2 x 2 x 2 mixed design experiment (between and within subject).  Experiment method of 2 x 2 x 2 includes disclosure pattern (step by step and end of sequence), evidence order (good news followed by bad news and bad news followed by good news), and Framing Effect (negative frame and positive frame). Research participants in this research are: non-professional investor and professional investor. The number of participants in this research is 274 people consisting of 154 participants from non-professional investors and 120 participants from professional investors.  The experiment was done by researcher in June to October 2015. The results showed framing effect, the order of presentation and the presentation of information patterns affect investors in making investment decisions. The contribution for financial accountancy literature is that this research tries to conduct reconstruction on puzzle of investment decision making model.